Transcript Assembly and Quantification by RNA-Seq Reveals Significant Differences in Gene Expression and Genetic Variants in Mosquitoes of the Culex pipiens (Diptera: Culicidae) Complex. Issue 1 (31st August 2020) - Kang, David S; Kim, Sungshil; Cotten, Michael A; Sim, Cheolho
Abstract: The taxonomy of Culex pipiens complex of mosquitoes is still debated, but in North America it is generally regarded to include Culex pipiens pipiens, Culex pipiens molestus, and Culex quinquefasciatus (or Culex pipiens quinquefasciatus ). Although these mosquitoes have very similar morphometry, they each have unique life strategies specifically adapted to their ecological niche. Differences include the capability for overwintering diapause, bloodmeal preference, mating behaviors, and reliance on blood meals to produce eggs. Here, we used RNA-seq transcriptome analysis to investigate the differential gene expression and nucleotide polymorphisms that may link to the divergent traits specifically between Cx. pipiens pipiens and Cx. pipiens molestus .